Pembakar Jambatan Antara Dua Negara: Sentimen Anti-Jepun dalam Filem Korea Selatan - Hassan, Asmadi; Kamarudin, Muhammad Muhsein (WILAYAH: The International Journal of East Asian Studies, 2025)
A film usually contains certain ideology which is able to influence the audience. The ideology in the film is neatly structured in order to be accepted by society naturally. This article discusses an anti-Japanese sentiment in South Korea films which are perceived as an ideology that ultimately damaging the bilateral relations of the both countries. Three films were selected to study the anti-Japanese sentiment in South Korea namely Spirit Homecoming, The Battleship Island and Anarchist from Colony. The selection of these films is based on the issues connected between the past and the current issues that have yet to be resolved. The first theme is the severe experience by the Comfort Women and the second is the poor treatment of Koreans who were taken/went to Japan during colonialism period. This study applies a qualitative approach which is the primary resources obtained from news reports and observation of the films. While secondary resources are from journal articles and books. The study found that the films have been responsible for the spread of anti-Japanese ideology to South Korean society. As a result, it has influenced the people and consequently causing hatred among them. It then resulted to damaging the relations between the two countries which has already been tension by the colonialism and current issues. Eventually, the film which was supposed to be used as a platform for the good relations between the two countries became burner to those relations.